The need for further integration of services to prevent mother-to-child transmission of HIV and syphilis in Mwanza City, Tanzania. (June 2015) - Balira, Rebecca; Mabey, David; Weiss, Helen; Ross, David Anthony; Changalucha, John; Watson-Jones, Deborah
Abstract: Objective: To assess the operational integration of maternal HIV testing and syphilis screening in Mwanza, Tanzania. Methods: Interviews were conducted with 76 health workers (HW) from three antenatal clinics (ANC) and three maternity wards in 2008–2009 and 1137 consecutive women admitted for delivery. Nine ANC health education sessions and client flow observations were observed. Results: Only 25.0% of HWs reported they had received training in both prevention of mother-to-child transmission (PMTCT) and syphilis screening. HIV and syphilis tests were sometimes performed in different rooms and results recorded in separate registers with different formats and the results were not always given by the same person. At delivery, most women had been tested for both HIV (79.4%) and syphilis (88.1%) during pregnancy. Of those not tested antenatally for each infection, 70.1% were tested for HIV at delivery but none for syphilis. Conclusion: Integration of maternal HIV and syphilis screening was limited. Integrated care guidelines and related health worker training should address this gap.